A Small Peptide Increases Drug Delivery in Human Melanoma Cells - Shirley Tong; Shaban Darwish; Hanieh Hossein Nejad Ariani; Kate Alison Lozada; David Salehi; Maris A. Cinelli; Richard B. Silverman; Kamaljit Kaur; Sun Yang (MDPI AG, 2022)
Melanoma is the most fatal type of skin cancer and is notoriously resistant to chemotherapies. The response of melanoma to current treatments is difficult to predict. To combat these challenges, in this study, we utilize a small peptide to increase drug delivery to melanoma cells. A peptide library array was designed and screened using a peptide array-whole cell binding assay, which identified KK-11 as a novel human melanoma-targeting peptide. The peptide and its D-amino acid substituted analogue (VPWxEPAYQrFL or D-aa KK-11) were synthesized via a solid-phase strategy. Further studies using FITC-labeled KK-11 demonstrated dose-dependent uptake in human melanoma cells. D-aa KK-11 significantly increased the stability of the peptide, with 45.3% remaining detectable after 24 h with human serum incubation. Co-treatment of KK-11 with doxorubicin was found to significantly enhance the cytotoxicity of doxorubicin compared to doxorubicin alone, or sequential KK-11 and doxorubicin treatment. In vivo and ex vivo imaging revealed that D-aa KK-11 distributed to xenografted A375 melanoma tumors as early as 5 min and persisted up to 24 h post tail vein injection. When co-administered, D-aa KK-11 significantly enhanced the anti-tumor activity of a novel nNOS inhibitor (MAC-3-190) in an A375 human melanoma xenograft mouse model compared to MAC-3-190 treatment alone. No apparent systemic toxicities were observed. Taken together, these results suggest that KK-11 may be a promising human melanoma-targeted delivery vector for anti-melanoma cargo.